Organizational Trust in the Age of the Fourth Industrial Revolution: Shifts in the Form, Production, and Targets of Trust. (January 2023) - Lumineau, Fabrice; Schilke, Oliver; Wang, Wenqian
In this essay, we argue that the advent of the Fourth Industrial Revolution calls for a reexamination of trust patterns within and across organizations. We identify fundamental changes in terms of (1) what form organizational trust takes, (2) how it is produced, and (3) who needs to be trusted. First, and most broadly, trust is likely to become more impersonal and systemic. Trust between actors is increasingly substituted by trust in a system based on digital technology. Second, in terms of trust production modes, characteristic- and institution-based trust production will gain in importance. Third, despite the move toward system trust, there will nonetheless be a need to trust certain individuals; however, these trustees are no longer the counterparts to the interaction but rather third parties in charge of the technological systems and data. Thus, the focal targets of interpersonal trust are changing.